Sample selectivity and the validity of international student achievement tests in economic research - Eric Alan Hanushek; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2010)
Critics of international student comparisons argue that results may be influenced by differences in the extent to which countries adequately sample their entire student populations. In this research note, we show that larger exclusion and non-response rates are related to better country average scores on international tests, as are larger enrollment rates for the relevant age group. However, accounting for sample selectivity does not alter existing research findings that tested academic achievement can account for a majority of international differences in economic growth and that institutional features of school systems have important effects on international differences in student achievement.
Keywords: I20; O40; C83; 330; sample selection; international student achievement tests; economic growth; educational production; Bildungsniveau; Benchmarking; Stichprobenverfahren; Statistischer Test; Bildungsökonomik; Bildungsforschung; Welt